SISTEM INFORMASI MANAJEMEN PROSES BISNIS GENERAL AFFAIRS BERBASIS WEB - Thomas Andreas; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Kawan Lama Sejahtera (hereinafter referred to as Kawan Lama Group) is a company founded in 1955 which was originally engaged in the field of Commercial & Industrial Equipment Supplier. Currently, the Kawan Lama Group is still expanding by opening new stores and increasing the number of employees. Of course along with this expansion will pose challenges to meet business needs. Therefore, we need a system that can meet these needs. The purpose of this application is to simplify business processes in the General Affairs division at PT. Kawan Lama Sejahtera, such as ordering uniforms, office stationery, assessing the quality of catering. The author proposes to design and manufacture a web-based system and write a thesis entitled